2014
DOI: 10.1111/bjd.12973
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tumour vascularization in cutaneous malignant melanoma: clinical implications

Abstract: Malignant melanoma represents < 10% of all skin cancers but is responsible for the majority of skin-cancer-related deaths. Metastatic melanoma has historically been considered as one of the most therapeutically challenging malignancies. Fortunately, for the first time after decades of basic research and clinical investigation, new drugs have produced major clinical responses. Angiogenesis has been considered an important target for cancer treatment. Initial efforts have focused primarily on targeting endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 198 publications
2
17
0
3
Order By: Relevance
“…The results confirmed an increase in LD-hist around melanoma compared with matched control skin, in keeping with previous reports in small studies and large metaanalyses [17,25]. The results also revealed a raised lymphatic density around benign melanocytic lesions (moles), compared with control skin.…”
Section: Raised Perilesion Immunohistochemical Lymphatic Density Was supporting
confidence: 91%
“…The results confirmed an increase in LD-hist around melanoma compared with matched control skin, in keeping with previous reports in small studies and large metaanalyses [17,25]. The results also revealed a raised lymphatic density around benign melanocytic lesions (moles), compared with control skin.…”
Section: Raised Perilesion Immunohistochemical Lymphatic Density Was supporting
confidence: 91%
“…13 Moreover, authors observed that chronic exposure to radiation produced a reduced inflammatory response against an acute challenge, as shown by the diminished synthesis capacity of PGE2 and TNFa, 13 both factors being involved in melanoma-associated angiogenesis. 7 The presence of solar elastosis in dermis is a marker of chronic sun exposure rather than acute UVB irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Several of these genetic alterations were also described to be involved in tumor-associated angiogenesis. 7 We performed a retrospective investigation aimed on evaluation of the differences in angiogenesis and lymphangiogenesis between melanomas arising on skin with and without signs of chronic sun-induced damage.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, additional endothelial-sprouting-independent mechanisms have been described, such as vascular cooption, intussusceptive angiogenesis, mosaic vessels, vasculogenesis, and/or vasculogenic mimicry [3]. …”
Section: Introductionmentioning
confidence: 99%